Tackle characteristics and injury in a cross section of Rugby Union football - McIntosh, A. S.; Savage, T. N.; McCrory, P.; Frechede, B. O.; Wolfe, R. (Medicine & Science in Sports & Exercise, 2010)
Background: The tackle is the game event in rugby union most associated with injury. This study's main aims were to measure tackle characteristics from video using a qualitative protocol, to assess whether the characteristics differed by level of play, and to measure the associations between tackle characteristics and injury.